Pengajaran Menulis Bahasa Indonesia untuk Mendorong Kompetensi Komunikatif Siswa - Anita Candra Dewi; Johar Amir (Journal of Humanities, Social Sciences, and Education, 2025)
Writing is a core competency in Indonesian language learning, playing a crucial role in developing students' communicative abilities. This study aims to analyze various approaches, strategies, and methods for teaching Indonesian writing that are effective in improving students' communicative competence in elementary and secondary schools. This literature review examines previous research from national and international journals, educational textbooks, and policy documents related to Indonesian language teaching. The analysis shows that writing instruction that emphasizes the writing process (writing process approach), project-based learning, and the application of digital technology significantly contributes to students' ability to convey ideas, utilize vocabulary, and organize text structures effectively. Furthermore, the integration of reading activities and classroom discussions has been shown to support the improvement of students' oral and written communication skills. This study emphasizes the importance of a holistic approach, which focuses not only on the technical aspects of writing but also on the development of critical thinking skills, creativity, and effective communication skills. In conclusion, structured, interactive, and contextualized writing instruction can optimally foster students' communicative competence. These findings provide implications for Indonesian language teachers in designing relevant and innovative writing learning strategies.